THE FUTURE OF IRAN-CHINA RELATIONS: AN ALLIANCE OR PURE COOPERATION? - A. B. Dolatabadi; R. Zarei (Сравнительная политика, 2018)
The future of the Iranian political relations with other countries  especially China in the post-nuclear-agreementera is of serious  importance in the Iranian foreign policy in the Rouhani  administration. Despite turbulences in the relations of the two  countries in recent years, theirs have been stronger than the trade  relations between Iran and western countries. For this reason, the  shift from ordinary to strategic relations between Iran and China is  attracting serious attention in the political circles in Iran. The  supporters argue for the present and future stance of China in the  international society and its constructive role during the western- imposed sanctions against Iran. The opponents refer to the poorer  Chinese technology as opposed to their Western rivals and to  ambivalent and at time anti-Iranian stances Beijing adopted in the  Iranian nuclear problem. The question this paper seeks to answer is  whether there is a possibility of the promotion of the relations of the  two countries in future and the possible obstacles in the way.